2019
DOI: 10.14746/jki.2018.13.12
|View full text |Cite
|
Sign up to set email alerts
|

The role of gender in the use of Hungarian address forms

Abstract: Forms of address are directly related to the nature of social relationships. The gender of the discourse partners, including the question whether they are of the same or different genders, thus has an impact on the use of forms of address. The goal of this paper is to highlight the major gender-related characteristics of Hungarian address practices by reporting on a comprehensive sociolinguistic study based on questionnaires and interviews. In line with the perspective of social constructivism, the gender-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…4 of languages are possible assets that can benefit students' language learning [9]. Multilingualism is the ability to speak and understand more than two languages by an individual or a group of people to meet the communicative needs of a particular situation 10 . Multilingual academic contexts are general in Pakistan, the students and teachers belong to different urban and rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…4 of languages are possible assets that can benefit students' language learning [9]. Multilingualism is the ability to speak and understand more than two languages by an individual or a group of people to meet the communicative needs of a particular situation 10 . Multilingual academic contexts are general in Pakistan, the students and teachers belong to different urban and rural areas.…”
Section: Literature Reviewmentioning
confidence: 99%
“…office, classroom). For instance, Hungarian address form was studied related to metapragmatic reflections which revealed that informants signaled a degree of formality, evaluated attitude based on the addressee, respect, degree of proximity/ closeness, variations in emotional distance, gender, age, and social status [10].…”
Section: Literature Reviewmentioning
confidence: 99%